The Quality of Snack Bar with Jack Bean Tempeh Flour and Red Dragon Fruit Albedo Extract Substitution - Devi Alvina; Yuliana Reni Swasti; Franciscus Sinung Pranata (agriTECH, 2026)
The snack bar is a grab-and-go food with wheat flour as the primary component. In this context, exploring alternative substitute ingredients is necessary to strengthen food security, reduce Indonesia’s dependence on wheat, and increase the nutritional content of snack bars. Generally, snack bars have a high-carbohydrate content. In this research, wheat flour was substituted with jack bean (Canavalia ensiformis) tempeh flour to enhance protein content, and red dragon fruit (Hylocereus polyrhizus) albedo extract was used to improve fiber content. Therefore, this research aimed to determine the chemical, physical, microbiological, and organoleptic properties, and to identify the best formulation of snack bars using jack bean tempeh flour and red dragon fruit albedo extract as substitutes. A Completely Randomized Design (CRD) method was used with four formulation treatments. The ratios of wheat flour, jack bean tempeh flour, and red dragon fruit albedo extract in the formulation were 100:0:0 (K), 80:15:5 (A), 65:25:10 (B), and 50:35:15 (C), respectively. Significant differences were analyzed on chemical, physical, and microbiological results using One-Way ANOVA and followed by a post-hoc Duncan Multiple Range Test (DMRT). The snack bar results ranged from 9.62-18.47%, 1.13-2.40%, 16.81%-19.53%, 6.01-9.76%, 52.56-65.26%, 0.96-11.24%, 2.09-11.27%, and 15.55-32.02 N moisture, ash, fat, protein, carbohydrates, insoluble fiber, soluble fiber contents, and hardness, respectively. The microbial test met the requirements for contamination according to the Indonesian Food and Drug Authority (BPOM). The best formulation for the snack bar was identified in treatment B (65:25:10).